On Dismounts, Twists, Somersaults, etc, or Why it is Difficult to do that Double Back Layout Somersault? - Prassas, S. (coachesinfo.com)
1 - Quantities influencing angular momentum are the rotational speed of the gymnast, the point about which the gymnast is rotating, and the gymnast's body configuration. 2 - Total body angular momentum is made up of the sum of the angular momenta of the body's segments. 3 - In the absence of external torques, such as in airborne skills like dismounts and somersaults, the angular momentum is constant, or it is "conserved". As a result, when body configuration changes, the angular speed also changes - in the opposite direction. 4 - Gymnasts utilize the principles/facts mentioned in #2 and 3 above to a) speed up or slow down the (total body) rotation by changing ("opening" or "closing", respectively) body configuration, and b) increase or decrease the rotational speed of a particular body segment by correspondingly decreasing or increasing the rotational speed of another body part. 5 - Gymnasts can generate twist(s) by utilizing asymmetrical motion of the arm(s) to create "tilt". The advantage of this technique to generate twists is that twist(s) can be safely stopped/removed before landing by reversing the arm motion. 6 - Gymnasts might utilize the conservation of angular momentum principle even when external torques are present. 7 - The only way to change angular momentum is by the application of an (external) rotary force (called torque) for a given time - a quantity called angular impulse. 8 - Successful execution of a (rotational airborne) skill requires a perfect balance between competing requirements: 1) height/time in the air and 2) enough rotation in a pre-determined body configuration, i.e., angular momentum. 9 - Angular momentum is as important to the beginner gymnast as it is to the elite. 10 - "Sticking" a dismount or an airborne tumbling skill is a very difficult task requiring a perfect combination of timing, body configuration, and body position at touchdown. Even in optimum conditions, gymnasts must be sufficiently conditioned to withstand the extremely high loads developed during the very small time available to them to stop body motion.